Improving the Sensory, Nutritional and Physicochemical Quality of Fresh Meat - Sichetti Munekata, Paulo Eduardo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The e-book and Special Issue "Improving the Sensory, Nutritional and Physicochemical Quality of Fresh Meat" is composed of six original papers about recent advances in the area of Meat Science about the effect of production system in lamb meat quality, the effect of animal feed supplements in cattle meat, treatment of cattle carcasses to improve tenderness, and the characterization of volatile compounds associated with sensory attributes. Moreover, studies regarding the developments in the processing of meat are also included in this publication.